2002
DOI: 10.1097/00005176-200211000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Ribonucleic Acid Hydrolysis by Intestinal Explants of Neonatal Piglets

Abstract: Background: Healthy human adults are able to hydrolyze dietary nucleic acids and nucleotides in the gastrointestinal tract, thus facilitating absorption of the resulting nucleosides. However, little is directly known of the ability of infants to hydrolyze nucleic acids early in life. Methods: Purified RNA (50, 100, 250, and 500 mg/L) in a suitable medium was exposed to jejunal explants of weaning piglets to determine if enzymes expressed by the explants were sufficient to hydrolyze the nucleic acid. Aliquots f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…Since the piglet intestinal explants were washed before culture, it appears the hydrolysis of RNA can be achieved in the absence of pancreatic ribonuclease and that enterocyte phosphodiesterase should be the main enzyme responsible for the hydrolysis. The present result confirms previous findings reported by our group (Rueda et al 2002). In addition, Kuchan et al (2000) studied the influence of purine intake on uric acid excretion in infants fed on soya infant formulas suggesting that healthy infants can digest RNA and subsequently absorb the ribonucleotides liberated.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Since the piglet intestinal explants were washed before culture, it appears the hydrolysis of RNA can be achieved in the absence of pancreatic ribonuclease and that enterocyte phosphodiesterase should be the main enzyme responsible for the hydrolysis. The present result confirms previous findings reported by our group (Rueda et al 2002). In addition, Kuchan et al (2000) studied the influence of purine intake on uric acid excretion in infants fed on soya infant formulas suggesting that healthy infants can digest RNA and subsequently absorb the ribonucleotides liberated.…”
Section: Discussionsupporting
confidence: 94%
“…The efficiency of these enzymes to catabolize RNA and NT to absorbable products on a quantitative basis needs to be further investigated. A previous study from our group showed that cells from the intestinal epithelium are capable of hydrolysing RNA (Rueda et al 2002).…”
mentioning
confidence: 96%
“…Ribonucleotides appear to play an important role in intestinal physiology. Dietary ribonucleotides are rapidly catabolized (39) in the intestinal epithelium (40,41), are efficiently absorbed into enterocytes as nucleosides and free bases (42), and were also shown to have discernible effects on intestinal vascular blood flow (43). Immune response to OPV primarily linked with efficient functioning of gut-associated immune cell populations may have been influenced by the presence of dietary ribonucleotides.…”
Section: Discussionmentioning
confidence: 99%
“…Although explants were only kept viable for a maximum of 24 h in this experiment, this period is suitable for the majority of studies focused at pathogen-host interactions [ 8 10 ]. In addition, the ability to manipulate the gas media that explants are exposed can benefit studies aimed at intestinal physiology [ 11 ] and nutrition [ 12 ] by simulating more closely the luminal gas environment normally observed in vivo. Although providing continual circulation, this setup uses considerably more culture media compared to a 6-well culture plate setup (3 mL vs 100 mL) to continuously provide explants with nutrients and with metabolite clearance by dilution.…”
Section: Resultsmentioning
confidence: 99%